Pelatihan Manajemen Usaha Es Puter Melalui Pemanfaatan Teknologi Digital Dalam Upaya Memperkuat Perekonomian Masyarakat Di Kecamatan Glagah Kabupaten Lamongan - Zulkifli Lubis; Abdul Ghofur; Kemal Farouq Mauladi (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2020)
Sales Ice Puterin the community so far generally still use the tradition always of course low productivity and the results are less hygienic. Because it is the Science Team Community Service of the Wijaya Putra University of Surabaya make appropriate technology tools/machine ice puter equipped electric motor. It is useful for UKM Partners Ice Puternamely Mr.Paiman and Mr.Suradi to increase productivity can certainly improve the welfare and new labor opportunities. With the appropriate Technology Equipment/ Machinery Ice Puteri's expected later UKM partners can increase production capacity, the result is more hygienic, more varied tastes, and able to manage their finance in an orderly and systematic. Keywords: Productivity, Machinery, Electric Motors, Production Capacity